Pemberdayaan Ekonomi Perempuan Melalui Pelatihan Sistem Fotovoltaik pada Budidaya Hidroponik dan Sekolah Kewirausahaan Digitalisasi Pemasaran Produk Olahannya Pada Ibu-ibu PKK Tlogoanyar Lamongan - saputra, Muhamad Ganda; Nuryati; Susanti, Inta (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
This PKK group has an important role in the economic growth of women in the RT 01 environment. Women as entrepreneurs are familiar in today's global era. Women entrepreneurs (womenpreneur) are considered women who start, establish, and manage commercial businesses. The purpose of holding Women's Economic Empowerment activities through Photovoltaic System Training in Hydroponic Cultivation and Entrepreneurship School Digitalization Marketing of Processed Products to PKK RT.01 Tlogoanyar Lamongan women is to improve the ability of women preneurs of RT 01 women in hydroponic plant cultivation as well as entrepreneurship and product marketing, especially digital marketing. This stage begins with the determination of baselines and socialization of activities in the target areas. At this stage, the fostered partners are given material in the form of a demonstration of the installation of tools, then the fostered partners independently install the tools. Application of Technology: At this stage, the PKM team and Partners prepare tools and materials along with the installation of systems that require assembly, namely on NFT systems and mini solar power plants on the land by the PKM and Partner teams. Assistance and Evaluation: The evaluation stage of Partners together with the PKM Team evaluates the entire process of hydroponic cultivation, product utilization and product marketing. Women's Economic Empowerment Activities Through Photovoltaic System Training in Hydroponic Cultivation and the Tlogoanyar PKK Marketing Digitalization Entrepreneurship School have been carried out well. Based on the results that have been carried out, it shows that the participants who are members of the Tlogoanyar PKK have increased their knowledge and skills after participating in the training.